Isolation and Identification of Plant-Growth Inhibitory Constituents from Polygonum chinense Linn and Evaluation of Their Bioherbicidal Potential - Thang Lam Lun; Arihiro Iwasaki; Kiyotake Suenaga; Hisashi Kato-Noguchi (Plants, 2023)
Polygonum chinense Linn. is a medicinal and invasive plant that belongs to the family Polygonaceae. The pharmacological activities and phytochemical constituents of Polygonum chinense are well reported, but the allelopathic effects and potent allelopathic substances of P. chinense remain to be investigated. Hence, this experiment was conducted to separate and characterize potentially allelopathic substances from an extract of the Polygonum chinense plant. The Polygonum chinense plant extracts highly suppressed the growth of cress (Lepidium sativum L.), lettuce (Lactuca sativa L.), barnyard grass (Echinochloa crusgalli (L.) P. Beauv.), and timothy grass (Phleum pratense L.) seedlings in a species- and concentration-dependent way. Two active substances were separated using a series of purification procedures and determined through spectral analysis as (−)-3-hydroxy-β-ionone and (−)-3-hydroxy-7,8-dihydro-β-ionone. These two compounds significantly suppressed the seedling growth of Lepidium sativum (cress) at concentrations of 0.01 and 1 mM, respectively. The extract concentrations necessary for 50% growth inhibition (I50 values) of the cress hypocotyls and roots were 0.05 and 0.07 mM for (−)-3-hydroxy-β-ionone, respectively, and 0.42 and 1.29 mM for (−)-3-hydroxy-7,8-β-ionone, respectively. These findings suggest that these two compounds are in charge of the inhibitory effects of the Polygonum chinense extract and may serve as weed control agents.